A novel nethod of extraction of blend component structure from SANS measurements of homopolymer bimodal blends - Smerdova, Olga; Graham, Richard Stuart; Gasser, Urs; Hutchings, Lian R.; De Focatiis, Davide S.A. (WILEY-VCH Verlag GmbH, 2014)
A new method is presented for the extraction of single chain form factors and inter-chain interference functions from a range of small angle neutron scattering (SANS) experiments on bimodal homopolymer blends. The method requires a minimum of three blends, made up of hydrogenated and deuterated components with matched degree of polymerization at two different chain lengths, but with carefully varying deuteration levels. The method is validated through an experimental study on polystyrene homopolymer bimodal blends with MA ≈ ½ MB By fitting Debye functions to the structure factors it was shown that there is good agreement between the molar mass of components obtained from SANS and from chromatography. The extraction method also enables, for the first time, to produce inter-chain scattering functions for scattering between chains of different lengths.